Utilization of Orange Peel (Citrus reticulata) and Mussel Shells (Perna viridis) Waste as Polymer Reinforcers for Brake Lining Materials - Isma Wulansari; Wahyuda Akbar; Afridon Dwi Putra Berutu; Diva Pahlevi Putra Aumee; Muhammad Seprianto (G-Tech: Jurnal Teknologi Terapan, 2026)
Environmentally friendly brake lining material uses a polymer composite reinforced with natural materials. Material testing of morphology, density, specific gravity, and swelling showed that composition significantly affects composite properties. Increasing the proportion of green mussel shell resulted in a rougher surface, higher density and specific gravity, and a significant decrease in swelling. The variation of paper, citrus reticulata, and perna viridis  0:50:50 had the highest degree of swelling (33.76%), while the variation of 75:12.5:12.5 showed the lowest value (0.17%), making it ideal for humid environments. The combination of orange peel and green mussel shell produces a lightweight, strong, and moisture-resistant material, making it an alternative, sustainable material for vehicle braking systems.